2005
DOI: 10.1016/j.ejcnurse.2005.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Does Smoking Affect Blood Pressure and Heart Rate?

Abstract: Background-Smoking is an important cardiovascular disease risk factor, but the mechanisms linking smoking to blood pressure are poorly understood. Methods and Results-Data on 141 317 participants (62 666 never, 40 669 former, 37 982 current smokers) from 23 population-based studies were included in observational and Mendelian randomization meta-analyses of the associations of smoking status and smoking heaviness with systolic and diastolic blood pressure, hypertension, and resting heart rate. For the Mendelian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 25 publications
5
22
0
1
Order By: Relevance
“…This is consistent with many other reports such as the longitudinal studies in Japanese49 and American men50 and a cross-sectional study in French men 51. In addition, smoking Jordanian men had a significantly higher blood pressure than their non-smoking counterparts 52. However, we also found that smoking had no influence on hypertension in women.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with many other reports such as the longitudinal studies in Japanese49 and American men50 and a cross-sectional study in French men 51. In addition, smoking Jordanian men had a significantly higher blood pressure than their non-smoking counterparts 52. However, we also found that smoking had no influence on hypertension in women.…”
Section: Discussionsupporting
confidence: 93%
“…Despite the strong relationship between smoking and elevated risk for cardiovascular disease [9,10], there is paucity and discrepancy about the long-term effects of smoking cessation on BP in already established hypertension [11,12,13]. …”
Section: Introductionmentioning
confidence: 99%
“…While it is not atypical to have a higher percentage of female students in a physical therapist educational program [58], the fact that females tend to exhibit greater levels of anxiety compared to males [1] [3] [4] [10], may have had an impact on our results and therefore future studies may want to further examine gender differences on anxiety outcomes. Another limitation to this study is that activity prior to the intervention was not controlled, such as engaging in exercise, consuming caffeine, smoking or other activities that can cause an increase in heart rate and blood pressure [59] [60]. Future studies may want to control for pre-intervention activity level as well as control for a history of hypertension and/or medications that may influence heart rate and blood pressure [59].…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation to this study is that activity prior to the intervention was not controlled, such as engaging in exercise, consuming caffeine, smoking or other activities that can cause an increase in heart rate and blood pressure [59] [60]. Future studies may want to control for pre-intervention activity level as well as control for a history of hypertension and/or medications that may influence heart rate and blood pressure [59]. General atmosphere is another consideration for future re-…”
Section: Discussionmentioning
confidence: 99%